On modelling and simulation of a manipulator under consideration of a jammed joint - Hoang, Nguyen Quang (Vietnam Journal of Mechanics, 2010)
In this paper, the modelling of a jamming process of a joint during the operation of a manipulator is presented. Based on the kinematic property of a jamming process, a motion law of the jammed joint is chosen. By introducing a matrix corresponding to jammed joint, the equation of motion of the system is restructured without re-deriving. Some numerical simulations are carried out to illustrate the proposed algorithm.